2016
DOI: 10.4047/jap.2016.8.2.94
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen peroxide pretreatment and heat activation of silane on the shear bond strength of fiber-reinforced composite posts to resin cement

Abstract: PURPOSETo evaluate the effects of hydrogen peroxide pretreatment and heat activation of silane on the shear bond strength of fiber-reinforced composite posts to resin cement.MATERIALS AND METHODSThe specimens were prepared to evaluate the bond strength of epoxy resin-based fiber posts (D.T. Light-Post) to dual-curing resin cement (RelyX U200). The specimens were divided into four groups (n=18) according to different surface treatments: group 1, no treatment; group 2, silanization; group 3, silanization after h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
2
7
0
4
Order By: Relevance
“…Another possible explanation for this as stated by Daneshkazemi et al (2016) might be the presence of residual oxygen by-products have inhibited the polymerization of CC. Previous studies have showed both similar ( Pyun et al, 2016 , Daneshkazemi et al, 2016 ) and contrary results ( Monticelli et al, 2006b , Yenisey and Kulunk, 2008 , Monticelli et al, 2006c , Vano et al, 2006 ). HPSBS group had the lowest bond strength, although SEM showed increased surface roughness as shown in Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Another possible explanation for this as stated by Daneshkazemi et al (2016) might be the presence of residual oxygen by-products have inhibited the polymerization of CC. Previous studies have showed both similar ( Pyun et al, 2016 , Daneshkazemi et al, 2016 ) and contrary results ( Monticelli et al, 2006b , Yenisey and Kulunk, 2008 , Monticelli et al, 2006c , Vano et al, 2006 ). HPSBS group had the lowest bond strength, although SEM showed increased surface roughness as shown in Fig.…”
Section: Discussionmentioning
confidence: 70%
“…FP and CC are usually used due to esthetic, easily placement and removal, minimal requirement of tooth structure removal, have a modulus of elasticity similar to dentin ( Aksornmuang et al, 2004 , Asmussen et al, 1999 ), single-visit and cost-effective procedure ( Bitter and Kielbassa, 2007 , Shori et al, 2013 , Pyun et al, 2016 ). A low incidence of root fracture and more repairable situations in the instance of failure have been reported with FP and CC system, which subsequently increase the survivability of the tooth as compared to cast post and core or zirconium posts ( Martinez-Insua et al, 1998 , Mannocci et al, 1999 , Akkayan and Gülmez, 2002 , Ferrari et al, 2000b , Ferrari et al, 2000a , Sarkis-Onofre et al, 2014 , Malferrari et al, 2003 , Cagidiaco et al, 2008 , Monticelli et al, 2008 , Yavirach et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Otro estudio únicamente utilizó la silanización para demostrar que esta incrementa la resistencia a la tracción del perno en 15,3MPa. (27), mientras que Puyn et al emplearon calor (80°C) después de la silanización, demostrando que este proceso incrementa la adhesión y que el uso de peróxido de hidrógeno no afecta en dicho proceso (19), al igual que lo probado por Samimi (24).…”
Section: Resultsunclassified
“…El empleo de pernos de fibra ha aumentado en la última década (11) dado que proveen buenos resultados estéticos y adecuada distribución de las fuerzas (14). Esto se debe a que su módulo de elasticidad es muy similar al de la dentina, por lo cual el riesgo de fractura de la raíz disminuye (19); sin embargo, uno de los problemas a largo plazo es el fracaso en la adhesión, la cual se puede dar por la desunión entre el perno y el agente cementante o, también, entre la dentina y el agente cementante, la que con frecuencia se produce por la fuerza de tracción (3,11,19).…”
Section: Base Teóricaunclassified
See 1 more Smart Citation